不同种群元宝枫种仁含油率及脂肪酸组成分析与评价Analysis and evaluation of oil content in seed kernel and fatty acid composition of Acer truncatum from different populations - 韩旻昊1，2，燕丽萍1，王因花1，任飞1，梁燕1，仲伟国1，孙超1，吴德军1 HAN Minhao1,2, YAN Liping1, WANG Yinhua1, REN Fei1, LIANG Yan1, ZHONG Weiguo1, SUN Chao1, WU Dejun1 (Zhongguo youzhi)
为探明不同种群元宝枫之间的变异程度，筛选优良种质资源，对山东、河北、陕西、江苏和安徽5个省份12个地区的元宝枫种群进行分析评价，测定其种仁含油率及脂肪酸组成，对其进行变异分析、相关性分析和聚类分析，并通过主成分分析法和隶属函数法对其进行综合评价。结果表明：12个地区的元宝枫平均种仁含油率为30.44%，遗传变异程度较高；元宝枫种仁油中主要脂肪酸平均含量排序为亚油酸（29.80%）>油酸（25.06%）>芥酸（18.76%）>二十碳一烯酸（8.62%）>神经酸（7.37%）>棕榈酸（4.75%）>硬脂酸（2.34%）>α-亚麻酸（1.45%），其中神经酸（8.38%）、硬脂酸（11.10%）和α-亚麻酸（17.08%）变异系数较高；山东海阳（12.59%）、山东泰安（11.22%）和山东济南（10.36%）元宝枫种仁含油率及各主要脂肪酸的平均变异系数较大；方差分析表明，种仁含油率和各主要脂肪酸在种群间均有极显著差异；种仁含油率与地理因子均无显著相关性，主要脂肪酸与温度、降水以及无霜期相关性较高；聚类分析将12个地区元宝枫分为3个类群；综合评价认为华北地区的元宝枫更具育种价值。综上，各种群元宝枫种仁含油率和脂肪酸含量存在较高程度的变异，可将其作为筛选元宝枫优良种质资源的物质基础。 In order to investigate the degree of variation among different populations of Acer truncatum and to screen for good germplasm resources, A. truncatum populations from 12 regions of Shandong, Hebei, Shaanxi, Jiangsu and Anhui were analyzed and evaluated. Firstly, the oil content in seed kernel and fatty acid composition were determined. Then variation analysis, correlation analysis, and cluster analysis were performed, and a comprehensive evaluation was conducted using principal component analysis and membership function values. The results showed that the average oil content in seed kernels of the 12 regions was 30.44%, with a high degree of genetic variation. The average contents of the major fatty acid components were as follows: linoleic acid (29.80%) > oleic acid (25.06%) > erucic acid (18.76%) > eicosaenoic acid (8.62%) > nervonic acid (7.37%) > palmitic acid (4.75%) > stearic acid (2.34%) > α-linolenic acid (1.45%), and the coefficients of variation of nervonic acid (8.38%), stearic acid (11.10%) and α-linolenic acid (17.08%) were higher. The average coefficients of variation of oil content in seed kernel and various main fatty acid from Haiyang, Shandong(12.59%), Tai′an, Shandong(11.22%) and Jinan, Shandong(10.36%) were higher. Analysis of variance showed that there were significant differences in the oil content in seed kernel and various main fatty acids among populations. There was no significant correlation between oil content in seed kernel and geographical factors, and the correlations between major fatty acid components and temperature, precipitation and frost-free period were high. Cluster analysis classified the A. truncatum from 12 regions into three clusters. The comprehensive evaluation concluded that A. truncatum in North China was more valuable for breeding. In summary, the oil content in seed kernel and fatty acid content of various populations of A. truncatum have a high degree of variability, which can be used as the material basis for screening the excellent germplasm resources.